PREPARATION OF POLYANILINE FREE STANDING FILM BY CONTROLLED PROCESSING AND ITS TRANSPORT PROPERTY - JEONG, SK; SUH, JS; OH, EJ; PARK, YW; KIM, CY; MACDIARMID, AG (ELSEVIER SCIENCE SA LAUSANNE, 1995)
Polyaniline(emeraldine base : EB) free standing films with different degree of cross-linking prepared from NMP solution were stretch-oriented at 110 similar to 180 degrees C up to l/l(0), = 4 then doped with 1N HCl. Free standing films of polyaniline doped with various functionalized acid such as camphorsulfonic acid (HCSA), dodecylbenzenesulfonic acid (HDBSA), methane sulfonic acid(HMSA) etc. were prepared in various solvents such as o-chlorophenol, chloroform, etc. Processing conditions were determined by measuring UV/Vis spectra of solution. Films prepared from these solutions showed the conductivities of 10(-1) similar to 220s/cm. To investigate the effect of molecular weight on the properties of polyaniline films, high molecular weight polyaniline (Mw similar to 309,000) was synthesized at similar to-30 degrees C. It was found that mechanical property, crystallinity, conductivity of the films depend on the drying process and type of solvent. Transport properties for various polyaniline free standing fims will be discussed from the results of DC, microwave conductivity and thermopower measurements.